Kinetika Reaksi Resin Immobilized Photocatalyst Technology (RIPT) TiO2 Sebagai Bahan Alternatif Pengolahan Limbah Cair Tahu - Anisa Amelia Atmadani; Euis Nurul Hidayah (Yayasan Literasi Sains Indonesia, 2022)
Liquid waste from the tofu industry contains a lot of organic matter, the high content of this organic material will result in high BOD and COD values ​​in the waters and can have a bad impact if not handled properly. One alternative that is commonly used to overcome this problem is to use a photocatalyst degradation method. This study aims to determine the reaction kinetics which includes the determination of the reaction rate constant and the reaction order in removing the COD content of the resin-immobilized TiO₂ photocatalyst. This study presents the reaction kinetics of RIPT with catalyst, TiO2, catalyst mass (10gr, 20gr, 30gr), and RIPT mass (5gr, 10gr, 15gr). This research was conducted by making immobilized TiO2 photocatalyst resin and then entering 1000 ml of tofu industrial waste and the obtained RIPT-resin into the reactor in which stirring occurred using a test jar. Based on the results of the study, the best value for the reaction rate constant was obtained by the mass variation of RIPT (15gr). Meanwhile, the best value constant of reaction rate was obtained by mass variation of 30 gram TiO2 catalyst, with the result that the reaction rate constant value of RIPT- and RIPT-TiO2 30 grams was 0.0101 minute-1.